Prostate cancer in Germany among migrants from the Former Soviet Union - Winkler, Volker; Holleczek, Bernd; Stegmaier, Christa; Becher, Heiko (Global health action, 2012)
Background : In Germany, prostate cancer is the leading cause of cancer and the third leading cause of death from cancer in males. We investigate prostate cancer in Gernmany among migrants from the Former Soviet Union (FSU) and compare them to indigenous German population with regard to prostate cancer incidence, mortality and longitudinal effects. Methods : Data were obtained from two migrant cohorts residing in the federal states of North Rhine Westphalia (n=34,393) and Saarland (n=18,619). Vital status was ascertained through local population registries. Causes of death were obtained from the federal statistical office or from local health authorities. Cancer incidence of the Saarland cohort was derived from the Saarland Cancer Registry using record linkage. Results : From 1990 to 2005 we observed 3360 deaths of which 28 were due to prostate cancer. In the Saarland cohort 35 men were diagnosed with prostate cancer during the respective period. Migrants had lower prostate cancer incidence (SIR 0.74 (95% CI: 0.52-1.03)) and mortality (SMR 0.57 (95% CI: 0.38-0.83)) compared to the German population. Multivariate analysis showed a strong age effect on incidence meaning young migrants (below age 60) were diagnosed significantly more often with prostate cancer compared to Germans of the same age. However, mortality did not show any effects. Discussion : Lower prostate cancer mortality and incidence among migrants may reflect an ongoing situation in the FSU. Additionally, longitudinal analysis did not reveal convergence of migrant prostate cancer to German rates as expected from lifestyle driven cancer sites. Therefore, our results support the hypothesis of a genetic effect on prostate cancer risk.